PENGARUH DESIGN PRODUK DAN INOVASI PRODUKTERHADAP KEUNGGULAN BERSAING (Studi Kasus PT. Kreasi Akrilik Medan) - Vina Ayu Pratiwi; Lukman Nasution (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
This study was conducted to determine whether there is influence between product design and product innovation to competitive advantage in the PT. PT. Kreasi Akrilik Medan Terrain and sample in research 214. The Data Analysis technique used is multiple linear regression using SPSS. Based on the results of the research can be known that the Design of the Product (X1) has a value of t count of 4,321, and t table of 1,65251. If compared with t then the result 4,321 > 1,65251, so it can be concluded that the design of the product and the positive effect signifikat of competitive advantage (Y). Innovation and product cost (X2) has a t value of 11,827 if compared with t table then the result 11,827 > 1,65251, so it can be concluded that product innovations have a positive and signofikat against leunggulan compete (Y) . The simultaneous design of product have influence of playing and signifikat of competitive advantage. Meaning hypothesis in this study is accepted, it is evident from the value of F count > F table (131,753 > the 3.04). The results of the coefficient of determination indicates that the product design and product innovation influence on the competitive advantage at 0.555, or 55.5%, while the rest of 45,5% influenced by other variables not examined in this study.